The Impact of IoT Supply Chain Integrated Blockchain Technology Advancements in the Healthcare Sector: A Literature Review - Nur Aini Alhamda; Aulia Zikri Rahman (Journal of Logistics and Supply Chain, 2022)
This literature review article focuses on an in-depth analysis of the Influence of Blockchain Technology Integrated with IoT in Healthcare Supply Chain. The purpose of this scholarly article is to formulate a strong hypothesis on how the advancement of blockchain technology affects the efficiency and effectiveness of supply chains in the healthcare sector. In order to achieve this goal, the research applied a meticulous desk research method, collecting references from various reliable online sources such as Google Scholar, IEEE, and other academic online media. The results outline the significant impact that the integration of blockchain technology and IoT can have in the context of the healthcare sector. The discussion in this article addresses how blockchain technology connected with the Internet of Things (IoT) can provide concrete benefits in optimizing the healthcare supply chain. The practical implications of the integration of these technologies are revealed in the form of improved operational efficiency, information transparency, more accurate product tracking, and reduced risk of human error.